Documentation, Human Rights and Transitional Justice - Baumgartner, Elisabeth; Hamber, Brandon; Jones, Briony; Kelly, Gráinne; Oliveira, Ingrid (Journal of Human Rights Practice, 2016)
The role of testimony and documentation is crucial to human rights work in transitional contexts. Such evidence is vital in societies seeking to deal with a pas
Other Publications

Truth Commission Archives as ‘New Democratic Spaces’: Table 1. - Jones, Briony; Oliveira, Ingrid (Journal of Human Rights Practice, 2016)
Other Publications

Basic principles on the role of archivists and records managers in support of human rights - International Council on Archives; Human Rights Working Group (International Council on Archives, 2016)

Against the Odds: CICIG in Guatemala - United Nations High Commissioner for Refugees (Refworld, 2016)
Refworld is the leading source of information necessary for taking quality decisions on refugee status. Refworld contains a vast collection of reports relating to situations in countries of origin, policy documents and positions, and documents relating to international and national legal frameworks. The information has been carefully selected and compiled from UNHCR's global network of field offices, Governments, international, regional and non-governmental organizations, academic institutions and judicial bodies.
Keywords: References - Boel et al. (2021); Archives and Human Rights

The Secrets in Guatemala’s Bones - Jones, Maggie (The New York Times, 2016)
In the face of death threats, a forensic anthropologist has spent two decades exhuming the victims of a “dirty” civil war. Now his work might help bring justice for their murders.
Keywords: Archaeology and Anthropology; Forensic Science; Guatemala; Guatemalan Forensic Anthropology Foundation; Human Rights and Human Rights Violations; Jones; Maggie; Peccerelli; Fredy (1971- ); References - Boel et al. (2021); Archives and Human Rights; Rios Montt; Efrain; War Crimes; Genocide and Crimes Against Humanity

Recuperative memory in Romanian post-Communist society - Mitroiu, Simona (Nationalities Papers, 2016)
This paper explores the idea of “recuperative memory” with respect to the process of coming to terms with the past after the fall of the Romanian Communist regime in 1989. Its method is to examine the mechanisms used by recuperative memory in order to re-appropriate the past and emphasize the inherently mediated and multifaceted nature of this process. Using various examples from oral testimonies, autobiographical writings, literary works, and cinema, the paper argues that the role of recuperative memory is not only to facilitate the process of coming to terms with the past, but also to offer the material necessary to sustain a viable politics of memory. This entails providing a platform for the intergenerational transmission of memory and knowledge for those who did not live under the Communist regime, filling in this way the intergenerational gap, despite the lack of political class engagement.
Keywords: References - Boel et al. (2021); Archives and Human Rights

Occasional Paper No. 1 Transitional Justice in Germany after 1945 and after 1990 - Romeike, Sanya (International Nuremberg Principles Academy, 2016)
Keywords: References - Boel et al. (2021); Archives and Human Rights

State Security: A Reader on the GDR Secret Police - Münkel, Daniela (Federal Commissioner for the Records of the State Security Service of the former German Democratic Republic, 2016)
Google-Books-ID: 39VjAQAACAAJ
Keywords: References - Boel et al. (2021); Archives and Human Rights

Press Conference by the Chief Cabinet Secretary October 14, 2016 (PM) - Suga, Yoshihide (Prime Minister of Japan and His Cabinet, 2016)
Keywords: References - Boel et al. (2021); Archives and Human Rights

Press Conference by the Chief Cabinet Secretary June 3, 2016 (PM) - Suga, Yoshihide (Prime Minister of Japan and His Cabinet, 2016)
Keywords: References - Boel et al. (2021); Archives and Human Rights

The History Problem: The Politics of War Commemoration in East Asia - Saito, Hiro (University of Hawaii Press, 2016)
Seventy years have passed since the end of the Asia-Pacific War, yet Japan remains embroiled in controversy with its neighbors over the war’s commemoration. Among the many points of contention between Japan, China, and South Korea are interpretations of the Tokyo War Crimes Trial, apologies and compensation for foreign victims of Japanese aggression, prime ministerial visits to the Yasukuni Shrine, and the war’s portrayal in textbooks. Collectively, these controversies have come to be called the “history problem.” But why has the problem become so intractable? Can it ever be resolved, and if so, how? To answer these questions author Hiro Saito mobilizes the sociology of collective memory and social movements, political theories of apology and reconciliation, psychological research on intergroup conflict, and philosophical reflections on memory and history. The history problem, he argues, is essentially a relational phenomenon caused when nations publicly showcase self-serving versions of the past at key ceremonies and events: Japan, South Korea, and China all focus on what happened to their own citizens with little regard for foreign others. Saito goes on to explore the emergence of a cosmopolitan form of commemoration taking humanity, rather than nationality, as its primary frame of reference, an approach increasingly used by a transnational network of advocacy NGOs, victims of Japan’s past wrongdoings, historians, and educators. When cosmopolitan commemoration is practiced as a collective endeavor by both perpetrators and victims, Saito argues, a resolution of the history problem—and eventual reconciliation—will finally become possible.The History Problem examines a vast corpus of historical material in both English and Japanese, offering provocative findings that challenge orthodox explanations. Written in clear and accessible prose, this uniquely interdisciplinary book will appeal to sociologists, political scientists, and historians researching collective memory, nationalism and cosmopolitanism, and international relations—and to anyone interested in the commemoration of historical wrongs.
Keywords: References - Boel et al. (2021); Archives and Human Rights

Routinised recognition and anxiety: Understanding the deterioration in Sino-Japanese relations - Gustafsson, Karl (Review of International Studies, 2016)
Why do interstate relations deteriorate and become conflictual, even under conditions where one might expect improved ties? The article seeks an answer to this question through a case study of the deterioration in Sino-Japanese relations in the twenty-first century, which took place despite the existence of several factors that might be thought likely to have led to an improvement. Existing theoretical approaches cannot fully explain this puzzle. The article argues that such deteriorations can result from disruptions to states' reciprocally performed routinised recognition, and identifies three mechanisms through which these can occur. To facilitate this argument, the article draws on scholarship on relational identity, recognition, and ontological security to develop a theory of identity construction that takes account of how self and other routinise the ways in which they recognise each other and how they react to the other's representational practices.
Num Pages: 21 Place: London, United Kingdom
Keywords: 21st century; Anxiety; Case studies; Identity; International relations; Ontology; Political Science–International Relations; Political theory; Power; References - Boel et al. (2021); Archives and Human Rights; Scholarship

Supported by France, Convicted by Africa France-Chad Relations during the Hissène Habré’s Rule (1982-1990) - Human Rights Watch (Human Rights Watch, 2016)
Keywords: References - Boel et al. (2021); Archives and Human Rights

US, France Backed Convicted Chad Dictator - Human Rights Watch (Human Rights Watch, 2016)
The United States and France were well aware of Hissène Habré’s brutal record, and yet continued to support him throughout his rule. Both countries should examine how and why they supported a man convicted of crimes against humanity.
Keywords: References - Boel et al. (2021); Archives and Human Rights

Enabling a Dictator: the United States and Chad's Hissène Habré 1982-1990 - Human Rights Watch (Organization) (Human Rights Watch, 2016)
"The report, 'Enabling a Dictator: The United States and Chad's Hissène Habré 1982-1990s,' describes how France, and especially the United States, were pivotal in bringing Habré to power, although signs of his brutality were already evident. The two countries saw Habré as a bulwark against the expansionist designs of Libyas Muammar Gaddafi, whose forces were occupying northern Chad. Human Rights Watch details how both the United States and France continued to provide Habrés government with critical support, even as it committed widespread and systematic human rights violations"–Publisher's description
OCLC: ocn953209701
Keywords: 1900-1999; 20th century; Atrocities; Chad; Crimes against humanity; Genocide; Habré; Hissein; Human rights; Politics and government; References - Boel et al. (2021); Archives and Human Rights; Social conditions; War criminals

Public Access to Information for Development: A Guide to the Effective Implementation of Right to Information Laws - Lemieux, Victoria L.; Trapnell, Stephanie E. (The World Bank, 2016)
ISBN: 9781464808791
Keywords: References - Boel et al. (2021); Archives and Human Rights

ICRC collects DNA to identify Lebanon's civil war dead - AFP (Yahoo!News, 2016)
The International Committee of the Red Cross has started collecting DNA samples to help identify thousands of people who disappeared during Lebanon's 1975-1990 civil war, the ICRC said Friday. The ICRC called on the Lebanese authorities to create a "national mechanism" to help match victims' bodies with their families. "It is more than 40 years since the events took place and we are still asking ourselves how we are going to give answers to the families," said Fabrizzio Carboni, the ICRC's chief in Lebanon.
Keywords: References - Boel et al. (2021); Archives and Human Rights

Truth-Justice-Reparations Interaction Effects in Transitional Justice Practice: The Case of the ‘Valech Commission’ in Chile - Collins, Cath (Journal of Latin American Studies, 2016)
Recent thinking and practice in transitional justice suggest that victims and societies hold indivisible, perhaps even simultaneous, rights to truth, justice and reparations after gross human rights violations. This article analyses the advantages and drawbacks of such holistic approaches to transitional justice, through a case study of Chile’s second oﬃcial truth commission, the ‘Valech Commission’. The article illustrates the politics of ongoing contestation about authoritarian era crimes in Latin America, showing how and why the commission was designed to deliver on certain truth-and-reparations obligations towards survivors of past state repression, while attempting to explicitly decouple truth revelations from judicial consequences. It also discusses the implications of associating truth-telling and reparations in a single instance, and in doing so contributes to debates about the potentially contradictory or counterproductive outcomes that may arise from the yoking together of truth, justice and reparations functions in transitional justice policy design.
Keywords: References - Boel et al. (2021); Archives and Human Rights

Basic Principles on the role of Archivists and Records Managers in support of Human Rights - International Council on Archives (International Council on Archives, 2016)
Keywords: References - Boel et al. (2021); Archives and Human Rights; References - Comma (2020 1-2); Archives and Human Rights

Statement by European RTI Community on the world’s First Official Access to Information Day! - Access Info Europe (Access Info Europe, 2016)
Madrid, 28 September 2016 - On the first officially-recognised International Right to Know Day , European civil society groups working on the right of access to information today raised concerns that a lack of government transparency is damaging democratic processes, thereby facilitating rising mistrust and demagogic populism in Europe. Recent monitoring by civil society
Keywords: References - Comma (2020 1-2); Archives and Human Rights

General comment No. 23 (2016) on the right to just and favourable conditions of work (article 7 of the International Covenant on Economic, Social and Cultural Rights) - United Nations (OHCHR, 2016)
Keywords: References - Comma (2020 1-2); Archives and Human Rights

Bahrain court orders main Shiite opposition group dissolved - Schreck, Adam (AP NEWS, 2016)
DUBAI, United Arab Emirates (AP) — A court in Bahrain ordered the country's main Shiite opposition group to be dissolved on Sunday, deepening a crackdown on dissent in the strategically important Western-allied kingdom. The order against al-Wefaq marks one of the sharpest blows yet against civil society activists in the Sunni-ruled island nation, which was rocked by widespread protests led by its Shiite majority demanding political reforms five years ago. Bahrain,...
Section: Bahrain
Keywords: References - Comma (2020 1-2); Archives and Human Rights

Iran's political paranoia includes children of foreign fathers - Alikarami, Leila (Al-monitor.com, 2016)
Iran’s civil code excludes children born to Iranian mothers and foreign fathers from Iranian citizenship, leaving tens of thousands of children in limbo.
Keywords: References - Comma (2020 1-2); Archives and Human Rights

Defusing Hate: A Strategic Communication Guide to Counteract Dangerous Speech - Brown, Rachel Hilary (United Holocaust Memorial Museum, 2016)
Keywords: References - Comma (2020 1-2); Archives and Human Rights

Saudi Arabia gives women the right to a copy of their marriage contract - France-Presse, Agence (The Guardian, 2016)
Kingdom’s justice ministry announces move to ‘protect the rights of the woman’, ending practice of only supplying document to husbands
Keywords: Islam; Middle East and north Africa; References - Comma (2020 1-2); Archives and Human Rights; Saudi Arabia; World news

P. C. Chang and the Universal Declaration of Human Rights - Roth, Hans Ingvar (University of Pennsylvania Press, 2016)
The Universal Declaration of Human Rights is one of the world's best-known and most translated documents. When it was presented to the United Nations General Assembly in December in 1948, Eleanor Roosevelt, chair of the writing group, called it a new "Magna Carta for all mankind." The passage of time has shown Roosevelt to have been largely correct in her prediction as to the declaration's importance. No other document in the world today can claim a comparable standing in the international community. Roosevelt and French legal expert René Cassin have often been represented as the principal authors of the declaration. But in fact, it resulted from a collaborative effort involving a number of individuals in different capacities. One of the declaration's most important authors was the vice chairman of the Human Rights Commission, Peng Chun Chang (1892-1957), a Chinese diplomat and philosopher whose contribution has been the focus of growing attention in recent years. Indeed, it is Chang who deserves the credit for the universality and religious ecumenism that are now regarded as the declaration's defining features. Despite this, Chang's extraordinary contribution has been overlooked by historians. Peng Chun Chang was a modern-day Renaissance man-teacher, scholar, university chancellor, playwright, diplomat, and politician. A true cosmopolitan, he was deeply involved in the cultural exchange between East and West, and the dramatic events of his life left a profound mark on his intellectual and political work. P. C. Chang and the Universal Declaration of Human Rights is the first biography of this extraordinary actor on the world stage, who belonged to the same generation as Mao Zedong and Chiang Kai-shek. Drawing on previously unknown sources, it casts new light on Chang's multifaceted life and involvement with one of modern history's most important documents.
Keywords: References - Comma (2020 1-2); Archives and Human Rights

News from the ICA Human Rights Working Group - 2016-12 (December) - Peterson, Trudy Huskamp (ICA, 2016)

News from the ICA Human Rights Working Group - 2016-11 (November) - Peterson, Trudy Huskamp (ICA, 2016)

News from the ICA Human Rights Working Group - 2016-10 (October) - Peterson, Trudy Huskamp (ICA, 2016)

News from the ICA Human Rights Working Group - 2016-09 (September) - Peterson, Trudy Huskamp (ICA, 2016)

News from the ICA Human Rights Working Group - 2016-08 (August) - Peterson, Trudy Huskamp (ICA, 2016)

News from the ICA Human Rights Working Group - 2016-07 (July) - Peterson, Trudy Huskamp (ICA, 2016)

News from the ICA Human Rights Working Group - 2016-06 (June) - Peterson, Trudy Huskamp (ICA, 2016)

News from the ICA Human Rights Working Group - 2016-05 (May) - Peterson, Trudy Huskamp (ICA, 2016)

News from the ICA Human Rights Working Group - 2016-04 (April) - Peterson, Trudy Huskamp (ICA, 2016)

News from the ICA Human Rights Working Group - 2016-03 (March) - Peterson, Trudy Huskamp (ICA, 2016)
Keywords: Mar'16 shows the link to Apr'16

News from the ICA Human Rights Working Group - 2016-02 (February) - Peterson, Trudy Huskamp (ICA, 2016)

News from the ICA Human Rights Working Group - 2016-01 (January) - Peterson, Trudy Huskamp (ICA, 2016)